Did Hippocrates really say that? - ağırman yılmaz, serra (Medicina Historica, 2024)
In this study, ten preventive medicine recommendations in Ibn Şerif's Yadigâr, attributed to Hippocrates, will be analyzed. However, these don't match Hippocrates' known advice, leading to confusion. Literature suggests these recommendations might be from Islamic physician Theyâzuk, not Hippocrates. This study aims to resolve this attribution confusion by analyzing and comparing the recommendations and clarifying their origin and authorship.